Effect of temperature on motility and chemotaxis of Escherichia coli. - Maeda, K (1976)
The swimming velocity of Escherichia coli at various constant temperatures was found to increase with increasing temperature. The frequency of tumbling had a peak at 34 degrees C and was very low both at 20 and at 39 degrees C. The swimming tracks near the surface of a slide glass showed curves, and the curvature increased the temperature. When the temperature of a bacterial suspension was suddenly changed, a transient change of the tumbling frequency was observed. A temperature drop induced a temporary increase in the tumbling frequency, and a quick rise of temperature, on the other hand, resulted in a temporary suppression of the tumbling. These dynamic responses to sudden changes of temperature was not observed in the smoothly swimming nonchemotactic strains bearing the mutations cheA and cheC and also in a mutant with the metF mutation under a smooth swimming condition.